Drivers and Barriers Implementing Green Logistics Among Logistics Companies in Selangor, Malaysia - Fen, Chen Chiaw; Kamaruddin, Nor Kamariah; Mohd Nor, Norasmiha (Research in Management of Technology and Business, 2020)
Nowadays, the environmental issue in Malaysia has become more severe due to the increase in environmental activities of human and industrial companies. Thus, one of the largest contributors of carbon dioxide (CO2) is freight transportation. Due to the increasing environmental awareness among the logistic sectors, most of the logistic companies preparatory to implement green logistics. Therefore, the purpose of this study is to identify what are the drivers and barriers in implementing green logistics among the logistic companies in Selangor, Malaysia. The population of the research is logistics companies in Selangor, Malaysia, which engaged with global business and ISO certified. The quantitative analysis was conducted in this study through a survey. The unit of analysis is the individual who employed in the logistics companies. Sampling random sampling was used in this study. The descriptive analysis was conducted to measure the drivers and barriers in implementing green logistics among logistics sectors in Selangor. Out of 113 sets of questionnaires distributed, only 105 sets were returned. The findings showed the highest mean value of 4.46 for drivers in implementing green logistics was "greener the environment of Malaysia". In contrast, “lack of government regulation and legislation” showed the highest mean value of 4.30 for barriers in implementing green logistics. Limitation in this study was time constraint and hawthorn effect. This study is vital as it will contribute a vital input and platform for decision-maker in implementing green logistics in Malaysia.